Tumor-derived exosomal lncRNA SNHG4 promotes triple-negative breast cancer progression by targeting XPO5 - Wang, Zhi-Wen; Yang, Hou-Sheng; Guo, Hong-Shan; Li, Yue-Ying; Zhong, Jin-Yun; Jiang, Shu; Li, Jia-Peng; Yang, Zhong-Yi; Zhou, Chuan-Yi; Wang, Jun; Liao, Xing-Hua; Mao, Lei (Frontiers in Oncology, 2025)
BackgroundTriple-negative breast cancer (TNBC) is the subtype of advanced breast cancer with the shortest survival time and the poorest prognosis, and treatment options are relatively limited. Exosomes, small extracellular vesicles enriched with bioactive molecules, are critical mediators of intercellular communication and have been implicated in cancer progression. The aim of this study was to investigate the molecular mechanism of exosomes promoting the proliferation and migration of TNBC.MethodsIn this study, exosomes were identified by Flow cytometry and transmission electron microscopy, and RNA sequencing (RNA-seq) was used to identify differentially expressed genes and downstream regulatory molecules in exosomes. RNA-seq results were supported by bioinformatics analysis and Western blot analysis. Functional assays including in vivo tumor formation, Colony formation Assay, Scratch migration and transwell assays were performed to study exosomes related phenomena and mechanism.ResultsSerum-derived exosomes from patients with TNBC can induce TNBC progression in vitro and in vivo. lncRNA SNHG4 was most significantly up-regulated in exosomes, and overexpression of lncRNA SNHG4 significantly promoted the proliferation and migration of TNBC cells. In addition, lncRNA SNHG4 promotes TNBC cell proliferation and migration by upregulating the expression of Exportin 5(XPO5). Silencing XPO5 can effectively attenuate the tumor-promoting effect of serum exosomes in TNBC patients. Mechanistically, lncRNA SNHG4 acts through XPO5-mediated pathways. Silencing XPO5 can effectively inhibit the tumor-promoting effect mediated by lncRNA SNHG4.ConclusionsTaken together, our study revealed that the exosome lncRNA SNHG4 exerts its oncogenic role by activating XPO5-mediated pathways, thereby regulating TNBC cell proliferation and migration. This can be considered as a potential target for TNBC molecular therapy.